Pressure, Targets, and Disguised Microcredit Fraud - Dian Irani Agustina; Nazaruddin Malik; Driana Leniwati (Journal of Accounting Science, 2026)
General background: Microcredit is vital for expanding access to capital for micro and small enterprises, but its rapid growth has increased the risk of fraud. Specific background: One common form is ‘masked credit’, whereby loans are granted to ineligible recipients but are still considered administratively valid due to pressure to meet credit disbursement targets. Knowledge gap: Previous research has focused primarily on methods of detecting fraud and the factors influencing it, meaning that a phenomenological understanding of the perpetrators’ experiences has not been fully explored. Objective: The objective of this study is to investigate how perpetrators experience pressure and justify fraudulent actions in microcredit practices using a phenomenological approach. Method: This study adopts a descriptive qualitative approach using a phenomenological design. Data collection was carried out through in-depth interviews with key informants and the examination of various documents relating to microcredit operational practices. Results: The findings of this study reveal that the demand to meet credit disbursement targets is a major factor contributing to fraudulent practices. Furthermore, accounting practices were found to function as an administrative tool capable of disguising problematic transactions so that they appear to meet formal requirements, even though they substantially involve elements of fraud. Novelty: This study expands the fraud triangle and fraud diamond theories by positioning accounting as a mechanism of symbolic and ethical legitimisation. Implications: These findings highlight the need to strengthen ethical governance, moral awareness and internal controls to prevent the normalisation of fraud in the microcredit banking sector.